An Integrative Serum Pharmacology-Based Approach to Study the Anti-Tumor Activity of B. paniculatum Aqueous Bulb Extract on the Human Hepatocellular Carcinoma Cell Line BEL-7404 - Feng, Xuesong; Ma, Guangyuan; Shi, Hailong; Wang, Yuewen; Chao, Xu (Frontiers in Pharmacology, 2020)
The herb Bolbostemma paniculatum (Maxim) Franquet (Cucurbitaceae family), also known as Tu-Bei-Mu (TBM) in Chinese, has shown curative effects to treat several types of cancer as an adjunctive therapy. Thereby we intend to find its effect on the human hepatocellular carcinoma (HCC) and to understand the pharmacological mechanism behind it. In this study, an integrative serum pharmacology-based approach linking serum pharmacology and bioinformatics prediction was employed. Firstly, we used the serum taken introgastrically from the rats dministered by TBM aqueous bulb extract to culture the HCC cell line BEL-7404 and detect its anti-tumor effects. Secondly, the TBM putative targets were predicted using the ETCM database and known therapeutic targets of NPC were collected from the OMIM database. Then, a TBM-HCC putative targets network was constructed using the DAVID and STRING databases. Thirdly, key gene targets were obtained based on topological analysis and pathway enrichment analysis. The expression of 4 representative key targets were validated by Western blotting. As a result, 36 TBM targets and 26 known therapeutic targets of HCC were identified. These key targets were found to be frequently involved in 13 KEGG pathways and 4 biological processes. The expression of four representative key targets: TP53, CASP3, BCL2 and BAX further supports the suppression of TBM on HCC. In general, our study shows the curative effects of TBM against HCC. By using this integrative approach, we may find novel potential therapeutic targets to suppress HCC using TBM as an adjunctive therapy. And it could also help us understand the mechanism of HCC treatments in response to TBM.